2016
DOI: 10.1021/acs.macromol.6b01347
|View full text |Cite
|
Sign up to set email alerts
|

Self-Assembly of n-Shaped Rod–Coil Molecules into Thermoresponsive Nanoassemblies: Construction of Reversible Helical Nanofibers in Aqueous Environment

Abstract: Amphiphilic coil–rod–coil molecules 1–3, consisting of an n-shaped rod building block and poly­(ethylene oxide) (PEO) with a degree of polymerization of 5 linked through a biphenyl unit as the coil segment, were synthesized. Molecule 1 self-assembles into lamellar and hexagonal perforated layer structures, in the crystalline and liquid crystalline phases, respectively. Remarkably, molecule 2 incorporating lateral methyl groups between the rod and coil segments spontaneously self-organizes into hexagonal perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
19
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 61 publications
2
19
0
Order By: Relevance
“…In addition, n-shaped molecules with a unique frame possessing reversible helical nanostructures were reported in our previous work. These molecules exhibit helix-handedness inversion upon thermal stimulation in aqueous solutions . However, the self-assembly and supramolecular chiral control of amphiphilic n-shaped compounds incorporating photochromic AZO units and oligoether chains stimulated by UV and heat in water environments have rarely been reported.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, n-shaped molecules with a unique frame possessing reversible helical nanostructures were reported in our previous work. These molecules exhibit helix-handedness inversion upon thermal stimulation in aqueous solutions . However, the self-assembly and supramolecular chiral control of amphiphilic n-shaped compounds incorporating photochromic AZO units and oligoether chains stimulated by UV and heat in water environments have rarely been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Supramolecular assemblies showing stimuli-responsive properties are appealing, which not only offer a convenient way to tune the assembled morphologies in situ through mediating the aggregation-driving forces with external stimuli but also afford the assemblies with intriguing stimuli-responsiveness as smart supramolecular materials. , Various stimuli have been applied for this purpose, including temperature, pH, oxidation, and even phosphorylation . Among them, thermoresponsive supramolecular assemblies are extremely interesting due to their easy tunability in aqueous solutions, which affords advantages of supramolecular chemistry for potential bioapplications …”
mentioning
confidence: 99%
“…34 Among them, thermoresponsive supramolecular assemblies are extremely interesting due to their easy tunability in aqueous solutions, which affords advantages of supramolecular chemistry for potential bioapplications. 35 As a typical class of aggregation-induced emission luminogen (AIEgens), propeller-shaped tetraphenylethene (TPE) has been demonstrated to be a key probe to follow the supramolecular assembly or characterization of the morphologies through aggregation-induced emission (AIE) 36,37 and even for direct visualizing the initial steps of self-assembly. 38,39 In the present work, we propose using TPE as the hydrophobic core for building up the supramolecular monomer through dendronization with hydrophilic 3-fold dendritic oligoethylene glycols (OEGs) via a dipeptide linkage to form a class of amphiphilic dendronized TPEs (Figure 1a) and elucidate their supramolecular chiral assembly in aqueous media containing THF as the good solvent and different fractions of water as the poor solvent.…”
mentioning
confidence: 99%
“…This may be attributed to the microseparation of rigid and flexible domains combined with the intermolecular interactions related to hydrogen bonds, and electrostatic, hydrophobic/hydrophilic and π – π interactions 29–36 . In related work, the current authors have also reported the construction of n‐shaped 37, 38 and bent‐shaped 39 rod–coil molecular assemblies in aqueous solutions. This was possible through slight modification of molecular structures, thereby demonstrating that the structure of molecules significantly affects the self‐organizing behaviour required to form various supramolecular nanoassemblies.…”
Section: Introductionmentioning
confidence: 71%